THE POTENTIAL OF BANDOTAN LEAVES (Ageratum conyzoides L.) AS AN IMMUNOSTIMULANT AND ANTIBACTERIAL AGENT IN AQUACULTURE: A REVIEW - Nur Ikhlas Syuhada; Ronal Kurniawan; Okta Rizal Karsih; M Irsyad Nur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Aquaculture intensification increases fish susceptibility to infectious diseases, prompting the search for natural alternatives to reduce dependence on synthetic chemicals. Bandotan leaves (Ageratum conyzoides L.) of the Asteraceae family contain secondary metabolites, including flavonoids, alkaloids, terpenoids, and saponins, with antibacterial, antioxidant, and immunomodulatory activities. This literature review aims to analyze the potential of bandotan leaves as a natural immunostimulant and antibacterial agent in aquaculture, focusing on their phytochemical content, mechanism of action, and safety. This study used a literature review method, conducting searches across national and international journal databases, university repositories, and research institute publications. The inclusion criteria included articles discussing the biological aspects, phytochemical content, antibacterial activity, immunomodulatory effects, physiological parameters, histology, and safety of bandotan leaves in the context of aquaculture. The results of the study showed that bandotan leaf extract effectively inhibited the growth of pathogenic bacteria in fish by disrupting cell membrane integrity and inhibiting bacterial enzymes. Its bioactive compounds enhance immune response, antioxidant activity, and reduce metabolic stress in fish. However, its application faces challenges in determining the optimal dosage, assessing histopathological effects, and managing potential respiratory distress at high concentrations. Further research is needed to optimize the formulation, understand the molecular mechanisms, and ensure the long-term safety of bandotan leaf use in sustainable fish farming systems.